Molecular mechanisms and signaling pathways related to brain metastasis in breast cancer - Liang, Zhuming; Mo, Yanan; Zhang, Yujiao; Yu, Yanjing; Ji, Yinan (Frontiers in Pharmacology, 2025)
Brain metastasis in breast cancer (BCBM) significantly threatens the survival and quality of life of patients, particularly those with triple-negative (TNBC) and HER2-positive subtypes. It involves complex molecular mechanisms and diverse signaling pathways. This review highlights recent research on the molecular mechanisms and signaling pathways of BCBM. The process of BCBM includes several key steps: local infiltration of cancer cells into the bloodstream and subsequent spread to the brain. They must then overcome the blood-brain barrier (BBB) to establish and grow in the brain. Multiple signaling pathways, including PI3K/AKT, STAT3, NF-κB, Notch, and Wnt are involved in this process. Overall, BCBM is a complex disease regulated by multiple molecular mechanisms and signaling pathways. To improve patient survival and quality of life, it is crucial to deepen research into the mechanisms of BCBM and explore new treatment targets and strategies. This will enhance our understanding of BCBM and lead to more effective treatments.